Biocontrol of Soft Rot of Chinese Cabbage Using an Endophytic Bacterial Strain - Cui, Wenyan; He, Pengjie; Munir, Shahzad; He, Pengbo; He, Yueqiu; Li, Xingyu; Yang, Lijuan; Wang, Biao; Wu, Yixin; He, Pengfei (Frontiers in Microbiology, 2019)
Soft rot caused by Pectobacterium carotovorum subsp. carotovorum (Pcc) is a major constraint in the production of Chinese cabbage. The objective of this study was to demonstrate that the causative agent Pcc may be successfully managed by Bacillus amyloliquefaciens KC-1, both in vitro and in vivo. Chinese cabbage seedlings were cultivated in organic substrate termed bio-organic substrate using a floating-seedling system with B. amyloliquefaciens KC-1. This approach was applied in a greenhouse to evaluate the management of soft rot. The results showed that the extent of soft rot, as well as the transmission of Pcc to the stem progeny and its survival in the rhizosphere, were reduced following inoculation with B. amyloliquefaciens KC-1. In contrast, the population diversity of B. amyloliquefaciens KC-1 persisted in the Chinese cabbage stems after germination. These findings revealed that B. amyloliquefaciens KC-1 was able to survive and suppress the growth of Pcc in Chinese cabbage and its rhizosphere, protecting the host from the pathogen. The use of B. amyloliquefaciens KC-1 throughout the growth period of plants may be an effective strategy for the prevention of soft rot in Chinese cabbage.